1974
DOI: 10.1111/j.1751-0813.1974.tb14055.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Pelvic Dimensions, Other Body Measurements and Dystocia in Dorset Horn Ewes

Abstract: Summary Fifteen live and 16 post slaughter measurements were recorded from each of 29 mature Dorset Horn ewes in an investigation of pelvic dimensions and their association with past history of dystocia or difficult birth amongst the ewes. For comparison with a breed having a low incidence of dystocia, similar measurements were recorded from 6 mature Border Leicester ewes with no previous history of dystocia. The range in size of the Dorset Horn pelves was considerable, with conjugate diameter being more varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The average birthweight of Heath Sheep, however, was only 2.7 kg and in Texel Sheep 4.5 kg. Quinlivan (1971) and Fogarty and Thompson (1974) proved also that internal pelvic dimensions are important in explaining parturition difficulties. McSporran and Fielden (1979) confirmed this in radiographic studies and they conclude that incompatibility in size between maternal pelvis and the lamb is largely responsible for the need for assistance at birth.…”
Section: Discussionmentioning
confidence: 94%
“…The average birthweight of Heath Sheep, however, was only 2.7 kg and in Texel Sheep 4.5 kg. Quinlivan (1971) and Fogarty and Thompson (1974) proved also that internal pelvic dimensions are important in explaining parturition difficulties. McSporran and Fielden (1979) confirmed this in radiographic studies and they conclude that incompatibility in size between maternal pelvis and the lamb is largely responsible for the need for assistance at birth.…”
Section: Discussionmentioning
confidence: 94%
“…The 8% larger pelvic opening for MR ewes agrees with the 9% larger body size (Knight & Hockey 1982) of MR ewes compared with Romney ewes. In Dorset and Border Leicester ewes, body length was correlated to both conjugate diameter and pelvic area (Fogarty & Thompson 1974).…”
Section: Discussionmentioning
confidence: 95%
“…The area of the pelvic opening of ewes with a history of dystocia was smaller than for ewes with no history of dystocia (Quinlivan 1971;Fogarty & Thompson 1974). McSporran & Fielden (1979) used radiographic pelvimetry to measure the conjugate and transverse diameters of groups of Romney ewes with and without a history of dystocia and of MR ewes.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that lighter lambs had higher dystocia rates. Dystocia can be a consequence of lamb birth weight, sire breed, dam pelvic conformation (Fogarty and Thompson, 1974), malpresentation, maternal overfeeding, or prolonged parturition (Sargison, 1997;Everett-Hincks et al, 2007). In addition, lambs that endure difficult births have trouble maintaining body temperature and have inhibited behaviors in teat searching and suckling (Eales et al, 1982).…”
Section: Discussionmentioning
confidence: 99%